Oh Minas Gerais: Questions about a "mineira" identity of performance (Revista da Tulha, 2019)
This article proposes a reflection on concepts commonly used in several speeches as markers of a regional identity in Minas Gerais and how this idea is present in the musical production of a musician from Minas Gerais, Toninho Horta, an artist who had a notable performance at Clube da Esquina, in 1970s and remains active. From an ethnography of a performance by the musician, elements are raised in order to raise traces that characterize the regional identity of Minas Gerais.